The horse and his boy - Lewis, C. S. (Clive Staples), 1898-1963 (Lewis, C. S. (Clive Staples), 1898-1963. Chronicles of Narnia, 1994)
A boy and a talking horse share an adventurous and dangerous journey to Narnia to warn of invading barbarians.